Guideline for obtaining valid consent for gastrointestinal endoscopy procedures. Issue 10 (20th June 2016) - Everett, Simon M; Griffiths, Helen; Nandasoma, U; Ayres, Katie; Bell, Graham; Cohen, Mike; Thomas-Gibson, Siwan; Thomson, Mike; Naylor, Kevin M T
Abstract : Much has changed since the last guideline of 2008, both in endoscopy and in the practice of obtaining informed consent, and it is vital that all endoscopists who are responsible for performing invasive and increasingly risky procedures are aware of the requirements for obtaining valid consent. This guideline is restricted to GI endoscopy but we cover elective and acute or emergency procedures. Few clinical trials have been carried out in relation to informed consent but most areas are informed by guidance from the General Medical Counsel (GMC) and/or are enshrined in legislation. Following an iterative voting process a series of recommendations have been drawn up that cover the majority of situations that will be encountered by endoscopists. This is not exhaustive and where doubt exists we have described where legal advice is likely to be required. This document relates to the law and endoscopy practice in the UK—where there is variation between the four devolved countries this is pointed out and endoscopists must be aware of the law where they practice. The recommendations are divided into consent for patients with and without capacity and we provide sections on provision of information and the consent process for patients in a variety of situations. This guideline is intended for use by all practitioners who request or perform GI endoscopy, or are involved in the pathway of such patients. If followed, we hope this document will enhance the experience of patients attending for endoscopy in UK units.